Are Celebrity Endorsements Worth It ? Evidence from Listed Firms in India - Singh, Jagandeep (Indian Journal of Marketing, 2017)
Use of celebrities for endorsing brands is a popular marketing tactic. Marketers tend to shell out mind boggling amounts to rope in celebrities for brand endorsements. Some Indian cricketers and Bollywood actors have become money minting machines as a result of this trend. The million-dollar question that begs an answer is : Are celebrity endorsements worth it? This question has intrigued many followers of marketing and has made the subject of celebrity endorsements a widely researched one. This paper explored the impact of celebrity endorsement announcements on the stock prices of the firms by examining 36 brand endorsement announcements. The celebrity endorsement announcements under study were made in India between 2008 and 2015. The standard event study methodology was followed to examine whether cumulative abnormal returns accrued to firms on the announcement day, (-1, +1) window, (-2, +2) event window, (-5, +5) event window, (-10, +10) event window, and (-40, +40) event window. The study found little evidence to establish that positive and substantial cumulative abnormal returns were accrued to firms when celebrity endorsement contracts were made public. Neither the firms in the consumer goods industry nor in the automobile industry were beneficiaries of celebrity endorsement contracts. The gender of the celebrity or the type of celebrity did not have any significant impact on the cumulative returns recorded by firms in different event windows at the time of announcement of such contracts. The returns recorded by firms that followed a corporate branding strategy as well as firms that followed a house of brands strategy were not statistically different from zero.